Regulating the expression and function of homeotic genes. - Dessain, S.; McGinnis, W. (Current Opinion in Genetics and Development, 1991)
Research published in the past year has led to plausible molecular models explaining the maintenance of stable patterns of homeotic gene expression through many cell generations. In addition, genes have been identified that modify the functional specificity of homeotic genes without affecting their expression patterns.